The adsorption and desorption processes of organic working fluids R1234yf, R134a, R32 in MOF-5 and Co-MOF-74: a molecular simulation study - Chen, Xinping (Frontiers in Energy Research, 2024)
The combination of nanoporous materials with organic working fluids holds the promise of further enhancing the performance of refrigerants based thermodynamics cycles. In this study, the adsorption and desorption properties of several organic refrigerants, e.g., R1234yf, R134a, R32, and their mixtures in metal-organic framework materials MOF-5 and Co-MOF-74 are investigated via molecular dynamics methods. The results indicate that the adsorption capacity is inversely proportional to the temperature during the adsorption process, and the adsorption capacity of the R1234yf/R32 mixture (molar ratio 2:1) is higher than that of the corresponding pure working fluids. The desorption amount, desorption regeneration rate, and desorption heat are directly proportional to the temperature. The interactions between different molecular atoms in the mixed working fluids promote the desorption process.